Biomass and vermicompost production by the earthworm Eudrilus eugeniae (Kinberg) - Mba, Caroline C. (1989)
Eudrilus eugeniae (Kinberg) was cultured in plastic pots containing ground Paspalum digitatum (L) grass (Dollis grass). This medium was toxic to the worms, if not fermented. Fermented and aerated grass were palatable. The worms fed and grew on the fermented-aerated grass and voided lack colloidal casts (vermicompost), similar to the casts normally voided on cassava peel diet. Transit of grass through the gut was rapid and varied with age: 4.5, 5 and 6 hours for hatchlings, juveniles and adults, respectively. The rate of cast and biomass production (worm/day) was high and varied with developmental stage. Biomass and casting production was higher with both juveniles and hatchlings. Fermented-aerated and non-fermented grass were toxic to the cocoons. Cocoon coagulation took place within 3 days of exposure with moist round grass, fermented-aerated or unfermented, while Dallis (worm castings) compost allowed normal development and hatching of the cocoons.